Jewish cult and Hellenistic culture: essays on the Jewish encounter with Hellenism and Roman rule - Collins, John J. (Journal for the study of Judaism, 2005)
A collection of twelve essays on the Jewish encounter with Hellenism, both in the Diaspora and in the land of Israel, including studies of several individual texts